Controle de plantas daninhas com herbicidas pré-emergentes na cultura do milho safrinha - Menegat, Luiz Felipe Müller (2024)
Weeds are considered a problem for current agriculture, as they compete for productive factors, increase costs due to resistance to herbicides, in addition to reducing the commercial value of products and causing a breakdown in land value. Weed control can be carried out in several ways, including chemical control, present in this work. Chemical control of weeds can be carried out through pre-emergent and/or post-emergent herbicides, these can be complementary to each other, in addition, to increase the spectrum of weed control, mixtures of active herbicide ingredients are made. In this context, the work aims to evaluate three pre-emergent herbicides for controlling weeds in corn (Zea mays) during the off-season. The experiments were implemented and conducted on the experimental farm of the Federal Technological University of Paraná located in the municipality of Dois Vizinhos - PR, from March 2023 to June 2023. The treatments tested are three preemergent herbicides, being pyroxasulfone + flumioxazine (Kyojin®), isoxaflutole + thiencoarbazone-methyl (Adengo®) and glyphosate – potassium salt (Xeque-Mate®), with four replications each. Weed control was evaluated using pre-emergent herbicides on soil covered with straw from the predecessor crop, soybeans, and bare soil. The variables analyzed were: number of weeds at 15, 30 and 45 DAE, dry mass of weeds, height of ear insertion in corn plants and height of corn plants at 15 and 30 DAE. The design to be used will be the Random Block Design (DBA). The collected data were subjected to analysis of variance and subsequently the means will be compared using the Tukey test at 5% probability. At the end of the experiment and subsequent statistical analysis, it was concluded that none of the treatments related to the use of pre-emergent herbicides showed a difference in the effectiveness of controlling weeds. However, the variable height of corn plants showed a difference in the covered soil in relation to the uncovered soil.